Reviving Pasir Sereh Tourism Village Patrol Village of Sukajaya Village, Cimerak District, Pangandaran Regency - Islamadina, Ari Wildan; Awalin, Bobi Nurul; Fadilah, Dida Sitti; Rumaesa, Dinda; Maulida, Hilma Putri; Vebrianti, Livia; Pramudya, Muhammad Adit; Aprilian, Muhammad Rivan; Fauziah, Nurlisyifa; Sholihah, Selvi Shofiatus; Athifah, Siti Nur; Wulansari, Wulansari; Apriansyah, Yossy; Sholihat, Neni (AbdimasMu UMTAS, 2025)
The Real Work Lecture (KKN-) at the University of Muhammadiyah Tasikmalaya was held in Sukajaya Village, Cimerak District, Pangandaran Regency. The tourism sector in Pangandaran has developed very rapidly, apart from that Pangandaran is referred to as a tourist area which has a variety of tourist attractions that are no less interesting to visit, namely beach attractions, rivers, hills, to waterfalls. One of the villages in Pangandaran, namely Sukajaya Village, Cimerak District, Pangandaran Regency, spoils the eyes of every visitor. But unfortunately the potential that has so far has not been utilized and neglected. Therefore the KKN- work program implemented is developing tourism potential in Sukajaya Cimerak Village through making several photo spots to attract the attention of tourists so that it can advance Karangjaya village and of course requires parties from village officials, villagers, and the regional tourism office.